Uji Streptomyces sp. Isolat Lahan Rawa Untuk Menekan Pertumbuhan Colletotrichum sp. Asal Cabai Rawit Varietas Hiyung Secara In Vitro - Alfi Sahriyanor; Mariana Mariana; Ismed Setya Budi (www.ulm.ac.id, 2024)
Hiyung chili is a local chili variety from South Kalimantan which is often attacked by anthracnose disease caused by the fungus Colletotrichum sp. The attack became severe because it was planted in swamp land. An environmentally friendly potential alternative for controlling anthracnose disease is using antagonistic agents from the bacteria Streptomyces sp. Streptomyces sp. bacteria isolated from 4 swamp lands in South Kalimantan, 2 lowland swamps and 2 tidal swamps. The research aims to determine the ability of Streptomyces sp. Swampland isolates inhibit the growth of the fungus Colletotrichum sp. origin of Hiyung chili in vitro. The research used a Completely Randomized Design (CRD) consisting of 16 treatments based on the origin of the isolates, 4 isolates from Sirang Laut, 4 isolates from Puntik, 4 isolates from Gudang Hirang and 4 isolates from Tajau Landung. Streptomyces sp bacteria. Isolated using selective Yeast Malt Agar media. The results of the exploration found 16 isolates of Streptomyces sp. and all isolates were able to inhibit the growth of Colletotrichum sp. with an inhibition percentage above 50%. The highest percentage of inhibition for isolates from Puntik was 96.44% and the lowest percentage for isolates from Sirang Laut was 51.95%. There were 8 isolates that produced clear zones in the inhibition test which was thought to be due to producing antibiotics, 1 isolate was hyperparasitic, and 7 isolates had an overgrowth mechanism.